Diffusion of glucose and sodium chloride in green olives during curing as affected by lye treatment - Maldonado, Mariela Beatriz (2008)
Green olives variety Arauco were debittered using lye concentrations of 2.00%, 2.50% and 3.00% of NaOH. Each treatment was then subjected to two rinsing processes with tap water. Next, the olives were cured with brine at 10% sodium chloride concentration. During this curing process, the loss of reducing sugars from, and the diffusion of sodium chloride into the olives was quantified. Effective diffusion coefficients of both solutes in the skin and the flesh were calculated for this period using a diffusion model for a composite hollow sphere. The debittering and rinsing processes, produced greater losses of reducing sugars from the olives with increasing lye concentration. The skin effective diffusion coefficients for both solutes ranged between 1.13x10_13 m2/s and 2.13x10_13 m2/s and were unaffected by lye concentration. The flesh coefficients varied between 2.50x10_09 m2/s and 4.05 x10_09 m2/s for sodium chloride and between 1.57x10_10 m2/s and 5.57x10_10 m2/s for reducing sugars and increased with increasing lye concentration. Considering the overall process (debittering/rinsing/curing), the extra time required for debittering with lye at 2.0% is amply compensated during the curing process in terms of release of reducing sugars (needed for the lactic fermentation) into the brine.